The awareness mandate of the Convention on the Rights of Persons with Disabilities as against intersectional stereotypes in the media on women with disabilities - Bregaglio Lazarte, Renata Anahí (2019)
This paper highlights the connections between representations of women with disabilities in mass media and the discrimination they face, in light of the State obligations derived from the Convention on the Rights of Persons with Disabilities (CRPD). The paper recognizes that this group faces intersectional forms of discrimination; because of this, the authors propose that a State obligation to prevent the perpetuation of stereotypes on gender and disability in mass media can be derived from a joint reading of CRPD and the Convention to Eliminate Discrimination Against Women. By analyzing representation in mass media, this paper finds that media outlets tend to convey false or protectionist stereotypes of women with disabilities. In consequence, the authors propose that responsible exercise of media-related professions should (i) reflect persons with disabilities’ demands for accessibility, (ii) highlight the positive impact of inclusive environments, (iii) include actors, actresses and role models with disabilities in advertisement and (iv) respond to the interests of persons with disabilities as consumers of their content.